You are on page 1of 11

(P)

f : [a, b] R

ϕ : [a, b] [ , ) L ([a, b]) U

⊂ K K

|f (t) f (s)| ≤ s ϕ(τ)dτ

t

t

s

t s

[ , ∞ ) L ([ a , b ]) U ⊂ K K | f

(P)

h(x(a), x(b))

(x, u) C ([a, b], R) × U

x(t) = u(t) +

(x(a), x(b)) A

t

λ

a

N(t, s)x(s)ds,

t [a, b]

A R h : R × R R

(x(a), x(b)) A

(P)

(x, u) C ([a, b], R) × U (P) (x, u)

x, u¯) (P)

hx(a), x¯(b)) h(x(a), x(b))

(x, u) (P)

) ( x , u ) (¯ x , u ¯) ( P ) h (¯

E f : [a, b] R n E ε > δ >

f

E

f (t) f (s) < ε

t, s [a, b] |t s| < δ

E f : [a, b] R n E E [a, b]

s ∈ [ a , b ] | t − s | < δ E f

f

δ > A µ(A) < δ

: [a, b] [ , ) L ([a, b])

>

A f (s)ds < .

E f : [a, b] R ϕ : [a, b] [ , ) L ([a, b])

|f (t) f (s)| ≤ s ϕ(τ)dτ

t

t s t s E

) L ([ a , b ]) | f ( t ) − f ( s

N(t, s) f : [a, b] R N

ts

t [a, b] s [a, t]

λ R

x(t) λ t N(t, s)x(s)ds = f (t)

a

N

s ∈ [ a , t ] λ ∈ R x ( t ) − λ

N f

x(t) = f (t) λ t H(t, s; λ)f (s)ds

a

H(t, s; λ)

H(t, s; λ) =

n=

λ n N n+ (t, s)

N n+ (t, s) = t N(t, z)N n (z, s)ds

s

N (t, s) N(t, s)

n = , ,

+ ( t , s ) = t N ( t , z ) N n

{f k } f k : [a, b] R f k f N : [a, b] × [a, b] R k x k (t)

x k (t) = f k (t) + λ t N(t, s)x k (s)ds.

a

{x k j } ⊂ {x k } x : [a, b] R x k j x x

x(t) = f (t) + λ t N(t, s)x(s)ds.

a

b ] → R x k j − x ∞ → x x ( t )

(P)

N : [a, b] × [a, b] R U (P)

(x, u) (P) (x i , u i ) (P)

{P} h(x(a), x(b))

{P} = h(x i (a), x i (b)).

{u i } u i u¯

{u i }

( b )) { P } = h ( x i ( a ) , x

{x i }

x i x¯

[a, b]

x¯ : [a, b] R

x¯(t) = u¯(t) + λ t N(t, sx(s)ds

a

x, u¯) (P)

(x i (a), x i (b)) A A x(a), x¯(b)) A

{P} = h(x i (a), x i (b))

= h(x i (a), x i (b))

hx(a), x¯(b)) {P}

x, u¯) (P)

b )) = h ( x i ( a ) , x i ( b ))